Komunikasi Anggota Keluarga Terhadap Sikap Penerimaan Pengasuhan Anak Berkebutuhan Khusus - Resman Muharul Tambunan; Tono Purwantoro; Des Hanafi (Jurnal Spektrum Komunikasi, 2025)
Effective communication between family members and children with special needs can improve understanding, support, and quality of daily interactions. Through open and responsive communication, family members can help children with special needs feel supported and valued and help them achieve their quality of life. Parents of children with special needs are very involved in all their children's activities and provide them with care. This study aims to determine the relationship between family communication, attitudes, and acceptance of caring for children with special needs. This study was designed using descriptive causality with a quantitative approach and a positivistic paradigm. The location of the study was the Jabodetabek area. Primary data were obtained directly from selected respondents through structured interviews using questionnaires. The measurement of sample size was carried out using Structural Equation Model Analysis - Partial Least Structural (SEM-PLS)-SmartPLS version 3. The results showed that family interpersonal communication had a significant relationship with attitudes of acceptance of caring for children with special needs. In addition, family communication patterns also influenced attitudes of acceptance, although the effect was minor compared to direct interpersonal communication.